2010
DOI: 10.1111/j.1751-9020.2010.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the Glass Ceiling at Work

Abstract: The glass ceiling is a popular metaphor for explaining the inability of many women to advance past a certain point in their occupations and professions, regardless of their qualifications or achievements. In this article, we review sociological research on glass ceiling effects at work. We discuss the current state of the glass ceiling, methodological and theoretical concerns with research in this area, and a number of the key factors that contribute to the creation and maintenance of glass ceiling effects, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 71 publications
2
35
0
2
Order By: Relevance
“…More senior women reported obstacles to formal promotion. These results corroborate research on women's workplace leadership experiences in STEM and other professions in the United States, and are indicative of widespread sociocultural constructions of gender roles whereby women are often perceived as unfit for or incompatible with leadership, and treated accordingly (Eagly & Carli, ; Purcell, MacArthur, & Samblanet, ).…”
Section: Discussionsupporting
confidence: 79%
“…More senior women reported obstacles to formal promotion. These results corroborate research on women's workplace leadership experiences in STEM and other professions in the United States, and are indicative of widespread sociocultural constructions of gender roles whereby women are often perceived as unfit for or incompatible with leadership, and treated accordingly (Eagly & Carli, ; Purcell, MacArthur, & Samblanet, ).…”
Section: Discussionsupporting
confidence: 79%
“…Women also face systematic disadvantages in terms of vertical mobility, authority and low-income, lower-status jobs (Purcell et al, 2010). Similarly, gender stereotypes exist as to what is considered "women's work" (Carrillo et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, Bonjour and Gerfin (2001) reveal that the gender wage gap is not constant throughout the wage distribution but it is larger at the bottom, even after controlling for gender differences in labour market characteristics for Switzerland. Harlan and Berheide (1994) identify systemic barriers to job advancement for women in a variety of occupations outside of white-collar occupations (Purcell et al, 2010). For instance, sticky floors are present in the manufacturing sector, where women are increasingly less likely to be represented within each level of the hierarchy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proportion of each component is the weight which also presented in the table 2(b). The formula for all the components used in calculating the final 'chief factors fraction' (F) is as shown in the equation (1). With the results from PCA, the value F in this study can be written as in equation (2).…”
Section: The Outcomes From the Principal Component Analysismentioning
confidence: 99%
“…This hypothesis hardly exists in reality. As Purcell et al [1] suggested, the constituted family reshapes an individual's social class through household integration and redistribution. Additionally, household exchange also impacts on the overall social resource distribution and social structure.…”
Section: Introductionmentioning
confidence: 99%